Aspect and the Biblical Hebrew Niphal and Hitpael - Benton, Richard Charles (My University, 2009)
This dissertation offers a new analysis of two derived Biblical Hebrew verbal forms, the Niphal and the Hitpael. Present scholarship on Biblical Hebrew does not agree on the definition of these two stems or the relationship of the stems to one another. As linguistic knowledge expands in the area of passive and middle voice and their interaction with situation aspect (i.e., the contrast between states and activities) new opportunities arise to analyze these verb forms. In Chapter 1 I outline the issues arising from the Niphal and Hitpael as parts of the Biblical Hebrew verbal system. The two major problems that exist are 1) providing unified definitions for each of the two stems, and 2) explaining the considerable overlap in meaning between the two. An analysis of the state of Hebrew scholarship on the Niphal and Hitpael comprises Chapter 2. I begin with the Niphal and the variation of its meanings, and then critique various methods by which these meanings have been systematized. Ultimately, I arrive at the stative/resultative meaning as definitive for the Niphal. I similarly analyze the Hitpael, looking at the various meanings offered for verbs in the Hitpael and critiquing models offered to unite these meanings. All the various meanings of the Hitpael share an activity sense in common. With these definitions in place, I examine explanations for the widely observed overlap between the meanings of the two stems. In Chapter 3, I develop a model for the interaction between grammatical voice and situation aspect. I approach the passive voice with a functional model in order to explain some of the phenomena that arise in the Biblical Hebrew Niphal and Hitpael, namely, the existence of more than one potential passive voice cross-linguistically and in Biblical Hebrew. Any passive construction demotes the primary argument, whether syntactically (position in the sentence) or topically (importance in the sentence). In this light, one can also classify the formal middle voice in many languages as fulfilling a passive function. While these formally distinct verb forms share this function, they each fulfill a distinct function within the passive voice, namely, the formal passive expresses a resulting state-oriented situation aspect, and the middle, an activity-oriented situation aspect. Chapter 4 demonstrates that the model of a passive voice bifurcated according to situation aspect as developed in Chapter 3 helps explain the Biblical Hebrew data. After I examine all the Niphal, Hitpael, Hitpolel, Hitpalpel, and Nitpael forms in the Hebrew Bible, I include examples in this chapter that contrast the two verb forms and that differ as little as possible in other details such as context and verb inflection. I also look at contrastive Pual forms to narrow down the areas in which the Niphal and Hitpael function. The examples are categorized in order to observe the effect of the number of participants and semantic class of the verb stem. Thus I am able to demonstrate that the Niphal and Hitpael both function as passives, whether they demote the primary argument syntactically or topically. This voice function explains the overlap between the stems. The Niphal operates as a state-oriented passive as is distinct from the Hitpael, which functions as an activity-oriented passive. This situation aspect function demonstrates the distinct semantic area that each stem covers. In Chapter 5 I compare the use of the Niphal and Hitpael from a diachronic perspective, from the earliest stages of Biblical Hebrew through Ben Sira. The Niphal reliably expresses a resulting state. The Hitpael appears to expand into more areas, as the number of Hitpael neologisms increases. Nevertheless, the Hitpael consistently expresses activity orientation.
Keywords: verb; aspect; exegesis; Hebrew language; historical linguistics